Efficiency of Social Studies Integrated Character Education Program - (:unkn) unknown (EDAM, 2011)
In this research, it is aimed to find out (i) the efficiency of a character education program based on overt values of Turkish 7th grade social studies lesson, and (ii) its hidden effects on the academic success. This research employed a semi-experimental design with pre-test, post-test and control group For this research primarily character education program and quantification tools were developed and then the practice process of the research was carried out. The practice of the research was made in a state primary school in Umraniye, Istanbul. Before the practice one of the classes is assigned as experiment and the other is as control group, equality of the groups has been determined through statistical progress. While character education program is being applied to the experiment group, normal course program has been applied to control group. The practice was continued totally 39 course hours being 3 course hours in a week.
Keywords: Character Education; Social Studies; Values Education